The structure of obsessive compulsive symptoms and beliefs: A correspondence and biplot analysis. (March 2016) - Kim, Se-Kang; McKay, Dean; Taylor, Steven; Tolin, David; Olatunji, Bunmi; Timpano, Kiara; Abramowitz, Jonathan
Highlights: Correspondence analysis with biplot was applied to examine the association between obsessive-compulsive symptoms and obsessive-compulsive beliefs. Samples of individuals with OCD ( N = 398), other anxiety disorders ( N = 104), and undergraduates ( N = 285) were collected. The results across three subsamples indicate that inflated responsibility was significantly associated with OC symptoms, for mild symptoms. Importance and control of thoughts were associated with OC symptoms across all levels of symptom severity. Abstract: Research has suggested that obsessive-compulsive (OC) beliefs are differentially predictive of OC symptom dimensions. One additional way in which beliefs and symptoms may be related is by severity; that is, the role of beliefs may vary as a function of symptom severity. In order to evaluate this possibility, correspondence analysis with biplot was applied to evaluate the association between OC beliefs and OC symptom severity across three subsamples, individuals with obsessive-compulsive disorder (OCD; N = 398), individuals with anxiety disorders ( N = 104), and undergraduate students ( N = 285). To do so, we generated five row categories of symptom severity and six columns based on the Obsessive Compulsive Beliefs Questionnaire (OBQ) for three subsamples. Unlike factor analyses of inter-variable correlations (or covariances), the CA-biplot paradigm calibrates simultaneously row and column information and estimates dimensional coordinates (analogous to factor loadings) separately for rows and columns. We used the first two dimensions from each subsample because they accounted for most variance (on average 89%) so as to construct a hypothetical plane with them. Then, we visually inspected associations among five severity categories (rows) and six OBQ subscales (columns) in the plane and also calculated their correlations. The visual configurations and numerical correlations were consistent across three subsamples, indicating that inflated responsibility was significantly associated with OC symptoms, but only for those with the least severe symptoms. Importance and control of thoughts were associated with OC symptoms across all levels of symptom severity. The implications of these findings for the cognitive model of OCD are considered.